Seismic Performance Assessment of Buildings: Influence of Material Type on Structural Response and Failure Modes - Asif Bashir; Amir Arshid (PT. Radja Intercontinental Publishing, 2025)
Seismic resilience remains a paramount concern in structural engineering, necessitating rigorous evaluations of material-specific performance under dynamic loading conditions. This study introduces a novel, data-driven comparative framework that evaluates the influence of material type—concrete, steel, composite, and timber—on the seismic response of buildings. Employing a dataset that integrates structural parameters such as displacement, stress, factor of safety, and failure modes, the research reveals distinct mechanical behaviors under seismic excitation. Results indicate that steel, despite its ductility and high stress tolerance, exhibits lower safety factors, making it prone to yielding under extreme loads. Concrete, while strong in compression, suffers from brittle shear failure. Composite materials balance strength and flexibility, exhibiting optimal behavior under seismic stress, while timber is susceptible to buckling, limiting its use in high-risk zones. The framework correlates seismic load, structural height, and deformation patterns, offering data-backed insights for seismic design codes and construction practices. This contribution aims to advance performance-based seismic design by integrating material-specific behavior into structural safety strategies.